(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Forms of educational organization mean the activities of teachers and students that are specially organized, in a specified order and in a specific mode. One or another organizational form of teaching is a combination of collective and individual teaching in various forms, different levels of independence of learners in teaching, different levels of teacher guidance of learners to study. described by methods.